Peningkatan Daya Saing Toko Safar Melalui E-Commerce dan Pemasaran Digital Berbasis Wix - Tirsa Ninia Lina; Matheus Supriyanto Rumetna; Wiesje Ferdinandus; Kusmiran Winandar, Aris (Yayasan Literasi Sains Indonesia, 2024)
Safar Store faces problems in the form of a lack of buyers due to increasing competition, limited marketing innovation, and less than optimal use of technology. To address these issues, the Community Service Program aimed to help Toko Safar increase its customer base through the use of e-commerce and digital marketing. The program employed various educational methods, including interactive workshops on website development using Wix Builder, digital marketing training, online order management education, and the introduction of Customer Relationship Management (CRM) strategies. The results showed that Toko Safar successfully established a functional e-commerce website with features such as a homepage, shop, cart, contact, search, and chat, which streamlined operations and enhanced customer experience. Additionally, the digital marketing training helped improve the store's online visibility and product promotion. The business owner expressed high satisfaction with the website implementation and the ongoing guidance provided. Overall, this program successfully delivered a long-term solution to improve Toko Safar’s competitiveness through digital innovation.